Civil disobedience and deliberative democracy - Smith, William. (Routledge innovations in political theory ;, 2013)
"Civil disobedience is a public, nonviolent, conscientious yet political act, contrary to law, carried out to communicate opposition to law and policy of government. This book presents a theory of civil disobedience that draws on ideas associated with deliberative democracy"--